Analysis and characterization of the X‐ray beam produced by a PF device for radiotherapy applications†. (20th May 2015) - Sumini, M.; Previti, A.; Galassi, D.; Ceccolini, E.; Rocchi, F.; Mostacci, D.; Tartari, A.; Pasi, F.; Facoetti, A.; Mazzini, G.; Nano, R.; Virelli, A.; et al.
<x xml:space="preserve">Abstract</x> A plasma focus device, devoted to the study of a possible application to the radiotherapy treatment of malignant cells, has been recently put into operation. The low‐energy (up to 200 keV) X‐rays are produced by conversion of the electron beam generated by the device during the pinch phase. The X‐ray spectrum has already been fully characterized, and an initial campaign of irradiation of specific cell cultures has been completed. At present, the links between the operational parameters of the actual device, the beam intensity, and the cell irradiation effects are being analyzed, trying to evaluate the advantage of the very high dose rate that can be delivered, of the order of several Gy in a few tens of nanoseconds. Preliminary results on radiobiological effectiveness are presented and discussed. Copyright © 2015 John Wiley & Sons, Ltd.